Granulite-facies beryllium pegmatites in the Napier Complex in Khmara and Amundsen Bays, western Enderby Land, East Antarctica - Grew, Edward S.; Yates, Martin G.; Barbier, Jacques; Shearer, Charles K.; Sheraton, John W.; Shiraishi, Kazuyuki; Motoyoshi, Yoichi (National Institute of Polar Research, 2000)
P(論文) Four granulite-facies beryllium pegmatites of Late Archean age intrude ultrahigh-temperature Napier Complex metapelites in Khmara Bay at "Christmas Point" and "Zircon Point" and in Amundsen Bay on Mt. Pardoe. The pegmatites evolved in three major stages. During the first stage, melt from anatexis of sapphirine-bearing metapelites soon after temperatures peaked during ultrahigh-temperature metamorphism crystallized as pegmatites in inter-boudin spaces during the waning stages of associated deformation. The primary carrier of beryllium in the pegmatites at the time of their intrusion was a sapphirine-group mineral. The second stage is high-temperature metamorphism at moderate pressure, which resulted in reaction of sapphirine with quartz to form corona assemblages of sillimanite+orthopyroxene (or garnet) in the host rocks and sillimanite+garnet+ surinamite in the beryllium pegmatites. Previous investigators have attributed the corona assemblages to isobaric cooling following ultrahigh-temperature metamorphism, but the relatively large size of the coronas and their deformation in the pegmatites suggests that the coronas formed in both the host rocks and the pegmatites during a separate tectonothermal event. The third stage includes two metamorphic events at lower temperatures and moderate to low pressures when surimanite broke down to beryllian cordierite±Al-poor orthopyroxene. The presence of late-formed kyanite and andalusite in the pegmatites is consistent with decompression inferred by other investigators for these two events. Beryllium in the Late Archean pegmatites could have originated from the host granulites, which at "Christmas Point" and Mt. Pardoe have average Be contents of 3.8±2.4ppm and 3.5±1.4ppm, respectively. Beryllium content of host-rock sapphirine is 61 to 616 times whole-rock Be content, implying an important role for this mineral in supplying Be to the anatectic melt. departmental bulletin paper